2022
DOI: 10.3390/ma15124098
|View full text |Cite
|
Sign up to set email alerts
|

A New Wire Electrode for Improving the Machining Characteristics of High-Volume Fraction SiCp/Al Composite in WEDM

Abstract: In wire electrical discharge machining, due to the random distribution of the insulating SiC particles, frequent wire rupture, low machining efficiency and surface quality when the common brass wire electrode (BWE) is used to process high-volume content SiCp/Al composite often appears. To address this issue, this paper proposes a new preparation method of zinc coating and surface microstructure on wire electrodes (ZCSMWE). The preparation process of ZCSMWE includes casting, coating, annealing and plastic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The average of all three values was then selected. Equation (1) was used to determine the MRR after the machining time was measured using a stopwatch [44,45].…”
Section: Methodsmentioning
confidence: 99%
“…The average of all three values was then selected. Equation (1) was used to determine the MRR after the machining time was measured using a stopwatch [44,45].…”
Section: Methodsmentioning
confidence: 99%
“…%) and Mg (0.05 wt. %) to increase the mechanical strength of brass alloys [6]. Nickel elements with a purity of >99 % and metallic aluminum powder with a purity level of >98 % are selected by the metal industry in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that there was a 35% increase in the wire feed rate along with a 40% reduction in wire consumption using coated wire compared to uncoated wire. Zei Chen [15] carried out an investigation on improving the characteristics of WEDM, and a comparison was made between copper wire and zinc-coated WEDM, and a 21.18% reduction in the wire wear rate along with a 16.67% improvement in the surface roughness were reported. Ruma et al [16] discussed the effects of three wire electrodes composed of plain brass wire, silver-coated brass wire, and zinc-coated wire on the machining of maraging 300 steel.…”
Section: Introductionmentioning
confidence: 99%